Germination ecology in orchids - Těšitelová, Tamara (Jihočeská univerzita, 2009)
Germination ecology of four Epipactis species (E. albensis, E. atrorubens, E. helleborine, E. purpurata) was studied. Habitat preferences of adult plants were analyzed using phytosociological relevés from the Czech Phytosociological Database. A field experiment was carried out to determine course of germination of Epipactis seeds sown in different habitat types. Relationship between ecological preferences and germination ecology, and spatial aspects of seed dispersal and seedling recruitment are discussed.
Germination ecology in orchids
Keywords: orchid; mycorrhiza; Epipactis; germination; PCR; orchid; mycorrhiza; Epipactis; germination; PCR